PENGARUH TENURE AUDIT DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL INTERVENING - Agustin Yustinawati Tiffani, 13.05.52.0192; Himmawan, Arief (Students' Journal of Accounting and Banking, 2017)
This research aimed to examine the influence of tenure audit and company size on the integrity of the financial statements with audit quality as intervening variabel. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period from 2013 to 2015. Sampling technique based on specified criteria namely purposive sampling. The relationship and influence between variabels or described using multiple regression analysis with path analysis. The result of the research shows that of tenure audit has a positive effect on integrity of the financial statements, while company size and audit quality have no effect on integrity of the financial statements. While the tenure audit and company size have a positive effect on audit quality.Keywords: Tenure Audit, Company Size, Audit Quality, Integrity of The Financial Statements